2015
DOI: 10.1007/s13277-015-3939-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TRIP6 promotes tumor proliferation and reverses cell adhesion-mediated drug resistance (CAM-DR) via regulating nuclear p27Kip1 expression in non-Hodgkin’s lymphoma

Abstract: Recent studies have identified that thyroid hormone receptor-interacting protein 6 (TRIP6) is implicated in tumorigenesis. However, the functional role of TRIP6 in non-Hodgkin's lymphoma (NHL) has never been elucidated. In this study, we demonstrated that TRIP6 is reversely correlated with the clinical outcomes of NHL patients. Western blot and immunohistochemical analysis revealed that TRIP6 expression is lower in indolent lymphoma than in progressive lymphoma. Kaplan-Meier survival curves indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Drug resistance remains an obstacle in achieving the optimal treatment of lymphoma (3). Increasing evidence has suggested that the bone marrow microenvironment protects lymphoma cells from apoptosis induced by cytotoxic drugs, including cell adhesion-mediated drug resistance (CAM-DR), leading to relapse following chemotherapy (5)(6)(7)(8). The emergence of CAM-DR remains a major obstacle for the successful treatment of lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance remains an obstacle in achieving the optimal treatment of lymphoma (3). Increasing evidence has suggested that the bone marrow microenvironment protects lymphoma cells from apoptosis induced by cytotoxic drugs, including cell adhesion-mediated drug resistance (CAM-DR), leading to relapse following chemotherapy (5)(6)(7)(8). The emergence of CAM-DR remains a major obstacle for the successful treatment of lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR pathway plays an important role on NHL growth and survival, data suggest that PI3Kδ inhibition can overcome prosurvival signals from the microenvironment that maintain NHL cells [4]. Lymphoma cells adhered to stromal cells are important in mediating tumor resistance to cytotoxic therapy (cell adhesion-mediated drug resistance (CAM-DR)) [5]. Previous studies have shown that the human bone marrow stromal cell adhered to Bcell lymphoma cells can protect NHL cells from rituximab cytotoxicity [6].…”
Section: Introductionmentioning
confidence: 99%
“…TRIP6 is one member of zyxin family of the LIM proteins and is one focal adhesion element with the capacity to the shuttle between cell nucleus and surface . TRIP6 was played roles in modulation of signal transduction and actin dynamics during cell migration and adhesion . Increasing studies showed that TRIP6 was expressed in neurons of hippocampal and regulated biological function of neurological .…”
Section: Discussionmentioning
confidence: 99%
“…38,39 TRIP6 was played roles in modulation of signal transduction and actin dynamics during cell migration and adhesion. 40,41 Increasing studies showed that TRIP6…”
Section: Discussionmentioning
confidence: 99%